Pengembangan Media Monopoli sebagai Sarana Belajar dan Bermain Siswa Sekolah Dasar dalam Materi Perkembangan Hewan dan Tumbuhan - Aditia, Rizky Regba; Ramazaan, Farroza Titis; Savilasari, Juwanda; Kurniawati, Wahyu; Husna, Anisya Al (Indo-MathEdu Intellectuals Journal, 2024)
The background is the need for an innovative approach in education to facilitate students' understanding of complex concepts. Monopoly media is developed to increase student engagement and facilitate understanding of concepts. Through interactive and interesting game elements. This study aims to develop Monopoly game-based learning media for animal and plant development material in Elementary Schools by applying the ADDIE model, which includes the analysis, design, and development stages. In the analysis stage, identification of needs and potential problems in learning is carried out. The design stage involves creating game components that are in accordance with the learning material. The development stage includes media production and validation, including the creation of game boards, question cards, and mystery cards. The subjects in this study were elementary school students, data collection techniques were carried out by interviewing and observing and data analysis was carried out using the Miles and Huberman data analysis techniques. The results of this development are expected to enrich students' learning experiences, improve collaboration, and motivate them in understanding animal and plant development material.